1987
DOI: 10.1159/000217525
|View full text |Cite
|
Sign up to set email alerts
|

Galactoside-Binding Lectin in Human Tissues

Abstract: Lactose-inhibitable lectin activity has been analyzed by hemagglutination assay in a variety of human tissues and cells obtained at surgery and autopsy. The lectin activity was detected in surgically removed melanoma, sarcoma, colon carcinoma, breast carcinoma, adjacent non-malignant tissues, non-malignant tissues obtained at autopsy and in cells isolated from malignant effusions. Although, on average, malignant tissue had a higher hemag-glutinating titer than non-malignant tissue, similar tissues from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
2
24
1
Order By: Relevance
“…9,11 This observation, however, is controversely discussed as Kamarashev et al 13 More recently, CD7 was shown to be a ligand of galectin-1 that initiates a signaling cascade resulting in apoptosis of CD7 + T cells. [18][19][20][21] Considering the rather abundant presence of galectin-1 in human tissues, 22,23 we assume that CD7-negative Sézary cells may be resistant to galectin-1-mediated cell death thereby favoring their accumulation within the tissues during progression of the disease. Using a panel of stimulation experiments we demonstrate here that CD7 − Sézary cells are resistant to galectin-1-induced cell death compared to neoplastic CD7 + T cells from patients with Sézary syndrome (SS) or non-SS leukemia.…”
Section: Cd45romentioning
confidence: 99%
“…9,11 This observation, however, is controversely discussed as Kamarashev et al 13 More recently, CD7 was shown to be a ligand of galectin-1 that initiates a signaling cascade resulting in apoptosis of CD7 + T cells. [18][19][20][21] Considering the rather abundant presence of galectin-1 in human tissues, 22,23 we assume that CD7-negative Sézary cells may be resistant to galectin-1-mediated cell death thereby favoring their accumulation within the tissues during progression of the disease. Using a panel of stimulation experiments we demonstrate here that CD7 − Sézary cells are resistant to galectin-1-induced cell death compared to neoplastic CD7 + T cells from patients with Sézary syndrome (SS) or non-SS leukemia.…”
Section: Cd45romentioning
confidence: 99%
“…One of the S-type lectins is frequently iso lated as a native ~ 30-kilodalton (kDa) di mer composed of identical ~ 14.5-kDa sub units [7,8]. For convenience, this lectin is defined here as galaptin, a term used pre viously to describe a larger group of lectins [9], Galaptin is present in a wide variety of human tissues as revealed by hemagglutina tion and immunodiffusion assays [8], and appears to be the product of a single gene [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We had previously reported the qualitative presence of galaptin in several body fluids, including serum and effusions, as detected by immunodiffusion [6].…”
Section: Discussionmentioning
confidence: 99%
“…The pres ence of galaptin in normal serum [9] and other body fluids [6] has been previously demon strated. However, the levels of galaptin were not quantified; nor was any information available on the presence of galaptin inhibi tors in body fluids.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation